Species diversity and population distribution of arboreal mammals in Kemuning Forest, Temanggung, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Krisanti AA, Widiyani T, Imron MA. 2017. Species diversity and population distribution of arboreal mammals in Kemuning Forest, Temanggung, Central Java, Indonesia. Biodiversitas 18: 1190-1195. Arboreal mammals which spent their life on the trees have significant roles for ecosystem balance and sustainability of forest ecosystem. This research aimed to reveal the diversity, population distribution, and the habitat used by arboreal mammals in Kemuning Forest of Bejen, Temanggung, Central Java, Indonesia. We conducted observation on the presence of arboreal mammals during four weeks started from April to July 2016. The observation was done within various times a day depends on the weather. 30 strips transect (ST) with 200m in length were established following the existing walking path for species identification. Point-quarter samplings (PQS) were used at every 50m of the track length for measuring diversity, density, and determining the dominant vegetation. There were 137 individuals of arboreal mammals detected and classified in 6 species, i.e., Callosciurus notatus, Ratufa bicolor, Galeopterus variegatus, Macaca fascicularis, Trachypithecus auratus, and Nycteris javanica. The largest population was M. fascicularis while the smallest was G. variegatus. There were 28 species of identified trees. Animals were observed in 22 tracks while the other six tracks were out of detected animals, so the relative frequency of animal was 80%. Diversity indices (H’) of the animal were 1.342, whereas the vegetation diversity indices were 2.795. Dominant vegetation species were Ficus macrophylla (36%). The arboreal mammals were distributed in a clumped pattern. We concluded that Kemuning Forest had the potential to be the suitable habitat for arboreal mammals with better managements.
Keywords: Arboreal mammals; distribution; diversity; Java